Relating to Deep Time Heritage: A Photovoice Approach to San Communities and Rock Art in South Africa - (:unkn) unknown (My University, 2025)
This presentation explores how present-day societies perceive Deep Time heritage, focusing on South African rock art sites. It questions whether rock art, often attributed to the San as a homogeneous group, holds significance for today’s San communities. Specifically, it examines how the Khwe and !Xun communities in Platfontein, South Africa, relate to rock art.The Khwe and !Xun share a history of war and displacement. During Namibia’s war for independence, many were recruited into the South African Defence Force to fight SWAPO. After SWAPO’s victory in 1990, about 500 individuals and their family relocated to South Africa, eventually settling in Platfontein, a farm containing rock engravings.Heritage institutions and tourism stakeholders have long promoted these engravings as meaningful to the San, given their ancestral origins. However, efforts to involve the Khwe and !Xun in heritage tourism at Wildebeest Kuil have not succeeded.In the framework of an international research project called COSMO-ART, a photovoice project, reversing previous approaches, was initiated to explore heritage from their perspective. By producing images and interviews, this co-constructed research process questioned what heritage truly means to them. This presentation outlines the photovoice process, and discusses its contributions to understanding Deep Time heritage in contemporary societies.
Keywords: African Research